Guru Besar sebagai 'role model' pemimpin kepada Guru Penolong Kanan Pentadbiran (GPK Pentabdiran) dalam memimpin sekolah - Jamari, Mohd. Rasidi (2013)
The purpose of this study is to identify whether the headmaster can be considered as a leader’s role model to the Senior Assistant Administration when leading the school. The data were collected from four Senior Assistants Administration from four primary schools in Kukup Zone, Pontian, who were selected based on three vital criteria’s ; school grade, UPSR achievement and the respondents’ experiences in the current schools. This study is an exploratory qualitative study and the data were collected by using an interview protocol that was self-designed to seek for their opinions on the headmasters’ leadership. The findings revealed that the headmaster was proven to be the most suitable leadership role model when leading the school. The findings also showed that main factor which contributing to the success of Senior Assistant Administration in leading the school is due to the contribution from headmaster as an informal mentor in coaching the Senior Assistant. Result also showed that there is a significant impact between the competency levels of the respondents with their success in leading the school. In this study, some suggestions have been forwarded for future researchers to improve and enhance the quality of management and administration in schools.